2005
DOI: 10.1161/circulationaha.104.477463
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Left Atrial Dissection Presenting as Pulmonary Edema

Abstract: A healthy 30-year-old man who had not had any prior medical or surgical history presented to the emergency department with substernal pain for 2 days that was sharp and exacerbated by inspiration and recumbency. Chest radiograph ( Figure 1A) showed mild left atrial enlargement. The ECG showed normal findings. The next day, the patient complained of sudden onset of class 3 dyspnea and frothy blood-tinged sputum. Follow-up chest radiography showed increased interstitial pulmonary vascular markings with consolida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Rarely, they occur spontaneously without any underlying conditions or procedures 5. RFCA is a relatively safe procedure, but has been known to be associated with some complications, including valvular injury, access site haematoma or injury, tamponade or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, they occur spontaneously without any underlying conditions or procedures 5. RFCA is a relatively safe procedure, but has been known to be associated with some complications, including valvular injury, access site haematoma or injury, tamponade or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of LA dissection were thought to be postoperative shear forces against the tissue between the mitral and aortic prostheses and marked tissue fragility due to systemic sclerosis and steroid treatment [14]. Spontaneous occurrence was seen in 11 patients [60,[62][63][64][66][67][68][69], including 2 patients primarily diagnosed with amyloidosis [61,65] and 2 patients with mitral annular calcification, which could have been the origin of the dissection in the LA wall [59,68]. Detailed information is summarized in Table 1.…”
Section: Pathogenesismentioning
confidence: 99%
“…It is generally associated with mitral valve replacement, but other predisposing factors should be considered in pathogenesis. 1,2 Atrial dissection-like appearance has been also reported 3 ; however, atrial dissection might be considered as an important differential diagnosis. Inferior sinus venosus (SV)-type atrial septal defect (ASD) is a rare congenital cardiac deformity that occurs between the inferior vena cava and right atrium.…”
mentioning
confidence: 98%
“…Left atrial dissection is defined as a gap from the mitral or tricuspid annular area into the interatrial septum. It is generally associated with mitral valve replacement, but other predisposing factors should be considered in pathogenesis . Atrial dissection‐like appearance has been also reported; however, atrial dissection might be considered as an important differential diagnosis.…”
mentioning
confidence: 99%